(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The great scientific and technical discoveries of the 21st century, the unprecedented development of information technologies and their integral part of public life, seem to have contributed to the fact that humanity has become more civilized and prosperous. However, in reality, on the way of their progress and development, people have faced a number of problems and challenges that threaten their normal life, deserve attention and require urgent solutions. Pedagogical science of health (pedagogical valeology), as one of the directions of health science, deals with the coverage of the above-mentioned problem, studying the issues of education and upbringing of a person with a healthy lifestyle. This is considered one of the greatest values that must be maintained and improved from the very first days of life. The preservation and strengthening of students ’ health, education and upbringing of a healthy person is one of the most important tasks of pedagogical valeology, since the progress and strength of the state and society are determined by the health of each of its members, which will contribute to the progress, development and enrichment of intellectual potential. In the modern world, rapid development of information technologies, increasing complexity of educational programs and overcrowding often lead to poor health of students, and sometimes even to a decrease in interest in learning. In connection with the above-mentioned problem, in this article we used the problem of preserving the health of the younger generation as a guarantee of a strong state and the progress of society.